The Effect of Project-Based Learning Model on Higher Order Thinking Skills of Senior High School (SMA/MA) Students for Biotechnology Material - Tanjung, Rika Muliana; Rasyidah, Rasyidah (Universitas Labuhanbatu, 2024)
The ability to think critically at the levels of analysis (C4), evaluation (C5), and concentration (C6) is known as Higher Order Thinking Skills (HOTS). The ability to discern high school students is really low, according to the researchers. The ability to monitor students at a higher level is weakened because students need a learning style or model that suits their needs in order to achieve their learning goals. With the ability to enhance students' HOTS, Project-Based Learning (PjBL) is a teaching methodology that may be applied to the biological sciences. Because of this, the research in this study used quantitative methods, namely the normality, Levene, and hypothesis tests that used t-tests (independent samples). They were derived from the results of the hypothesis test. The results of this study show that the PjBL learning model significantly affects high-level students' understanding of biotechnology material, with a p-value of 0.000 and a p-value of less than 0.05 (refer to equation 2)